2020
DOI: 10.3390/w12030660
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Modeling and Simulation of Water Residence Time in the Estuary of the Lower Amazon River

Abstract: Studies about the hydrodynamic behavior in the lower Amazon River remain scarce, despite their relevance and complexity, and the Water Residence Time (Rt) of this Amazonian estuary remains poorly unknown. Therefore, the present study aims to numerically simulate three seasonal Rt scenarios based on a calibrated hydrodynamic numerical model (SisbaHiA) applied to a representative stretch of the lower Amazon River. The following methodological steps were performed: (a) establishing experimental water flow in natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 75 publications
4
15
0
10
Order By: Relevance
“…The value of the constituents was imposed in the nodes of the open boundary using adjustment of coefficients (in amplitude and phase) for each harmonic constituent. A similar methodology was used in [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…The value of the constituents was imposed in the nodes of the open boundary using adjustment of coefficients (in amplitude and phase) for each harmonic constituent. A similar methodology was used in [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…The depth of the water body and flow velocity limit the exploitation of monogenean species in the host fish (Negreiros et al, 2018). In P. ornatus of the Amazon River, an environment with a high average water flow (1.0 x 10 5 m 3 /s), which prevents the accumulation and permanence of pollutants and eutrophication (Abreu et al, 2020), and with a high level of oxygen, there was a low level of infection by monogeneans Demidospermus sp. Negreiros et al (2018) reported that anthropogenic development of the Rio Acre influenced the levels of infection by Demidospermus peruvianus Mendoza-Palermo & Scholz, 2011;Demidospermus striatus Mendoza-Palermo & Scholz, 2011;Demidospermus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by Neves & Tavares-Dias (2019) for Ageneiosus ucayalensis (Castelnau, 1855), Pimelodella eigenmanni (Boulenger, 1891), Colomesus asellus (Muller & Troschel, 1849), Pimelodus blochii (Valenciennes, 1840), P. ornatus, Platynematichthys notatus (Jardine, 1841) and Peckoltia lineola (Armbruster, 2008) from Matapi River, a tributary of the Amazonas River, in Amapá State (Brazil). This absence of parasitic crustacean species may be due to the water velocity and daily tides from the Amazonas River (Abreu et al, 2020), given that these ectoparasites need to swim to find adequate hosts, while others depend on the flow of water and swimming speed (Neves & Tavares-Dias, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Physical-chemical variables in Araguari River -Maré Channels -Amazonas River recorded significant differences, mainly during the dry season (reduced dilution capacity) (Abreu et al, 2020), with emphasis on variables associated with increased solids contents in lotic aquatic ecosystems, namely: EC, TDS, Turbidity, S SC and Transparency (Tables 2 and 3).…”
Section: Table 1 Tablementioning
confidence: 99%
“…Water and sediment transport balances (Figures 4 and 7) have suggested high hydrological and hydrosedimentometric complexity in the region, as well as identified accelerated Urucurituba Channel evolution, which not only resulted in the expansion of a main drainage channel, but induced severe erosion processes, as well as uncontrolled branching of several waterbodies and of their connections. For example, Gurijuba-Igarape Novo Channel stands out for its connection to Urucurituba Channel, given the presence of interconnected branches that increase the flow direction complexity, since these flows interact with each other, are chaotically distributed across the floodplain and get intensified by the tidal regime (Gallo and Vinzon 2015;Abreu et al, 2020). However, they remain intense even during the dry period, when the connection between floodable fields and the main system still influences the ecological dynamics in the region .…”
Section: Net Discharge and Erosive Potentialmentioning
confidence: 99%